The human platelet transcriptome and proteome is altered and pro-thrombotic functional responses are increased during prolonged hypoxia exposure at high altitude. (2nd January 2020) - Shang, Chunxiang; Wuren, Tana; Ga, Qing; Bai, Zhenzhong; Guo, Li; Eustes, Alicia S.; McComas, Kyra N.; Rondina, Matthew T.; Ge, Rili
Abstract: Exposure to hypoxia, through ascension to high altitudes (HAs), air travel, or human disease, is associated with an increased incidence of thrombosis in some settings. Mechanisms underpinning this increased thrombosis risk remain incompletely understood, and the effects of more sustained hypoxia on the human platelet molecular signature and associated functional responses have never been examined. We examined the effects of prolonged (≥2 months continuously) hypobaric hypoxia on platelets isolated from subjects residing at HA (3, 700 meters) and, for comparison, matched subjects residing under normoxia conditions at sea level (50 meters). Using complementary transcriptomic, proteomic, and functional methods, we identified that the human platelet transcriptome is markedly altered under prolonged exposure to hypobaric hypoxia at HA. Among the significantly, differentially expressed genes (mRNA and protein), were those having canonical roles in platelet activation and thrombosis, including membrane glycoproteins (e.g. GP4, GP6, GP9 ), integrin subunits (e.g. ITGA2B ), and alpha-granule chemokines (e.g. SELP, PF4V1 ). Platelets from subjects residing at HA were hyperactive, as demonstrated by increased engagement and adhesion to fibrinogen, fewer alpha granules by transmission electron microscopy, increased circulating PF4 and ADP, and significantly enhanced clot retraction. In conclusion, we identify that prolonged hypobaric hypoxia exposure due to HA alters the platelet transcriptome and proteome, triggering increased functional activation responses that may contribute to thrombosis. Our findings may also have relevance across a range of human diseases where chronic hypoxia, platelet activation, and thrombosis are increased.